(untitled) (Bangladesh Journal of Medical Science, 2016)
Objectives: Postgraduate medical training is characteristically intensive and stressful. Given that anxiety disorders are often linked with stress-related scenarios; awareness of the burden of anxiety disorders among postgraduate medical trainees and their determinants is essential for informed intervention. This study was set to investigate the pattern of anxiety psychopathology, and to determine its correlates among doctors in a Nigerian postgraduate medical training facility. Methods: The participants, made up of 204 resident doctors were administered questionnaire to elicit their socio-demographic and work related variables. Subsequently, 12- item General Health Questionnaire (GHQ-12) was used to ascertain the presence of emotional distress, and the Structured Clinical Interview for Diagnostic & Statistical Manual for Mental Disorders- fourth edition [DSM-IV] Axis-1 Disorders, Non-patient edition (SCID-1/NP) was administered to characterize anxiety related psychopathology in the participants. Results: The mean age of participants was 33.44 (±4.50). In all, 120 (58.8%) respondents reported various difficulties with their examinations, 14(8.3%) reported having physical disorder and 59(28.9%) respondents were emotionally distressed. The prevalence of anxiety psychopathology based on DSM-IV criteria was 13.2% and the pattern elicited based on recognised categories include generalized anxiety disorder (4.9%), obsessive-compulsive disorder (3.4%), specific phobia (2.4%), social phobia (1.5%) and substance induced anxiety disorders (1.0%). Having additional qualification to the medical degree seems protective against anxiety psychopathology (?2= 3.91; df=1; p<0.05), while those with emotional distress (?2=17.54; df=1; p<0.001) were more likely to experience anxiety. Conclusion: Comprehensive and need-based mental health services with psychosocial support for trainee doctors are implied. Future research focusing on modifiable predictors of mental health challenges among resident doctors and their linkage with specific aspects of training is indicated. Bangladesh Journal of Medical Science Vol.15(1) 2016 p.25-32